PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA BAGI HASIL TERHADAP ALOKASI BELANJA MODAL DENGAN PERTUMBUHAN EKONOMI SEBAGAI VARIABEL MODERATING PADA PEMERINTAH DAERAH KABUPATEN/KOTA PROVINSI JAWA TIMUR TAHUN 2013-2015 - Wany, Eva (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2017)
This research aimed to examine the effect of regional real revenue, general allocation fund and revenue sharing fund on capital expenditures, as well as the effect of regional real revenue, general allocation fund and revenue sharing fund with moderation of economic growth in capital expenditure. This research was conducted at the distric/city in the province of east java. The sampling technique used was purposive sampling, and there are 36 district/city in province of East Java into the sample. This research used the realization of budget reports anda PDRB tables from 2013-2015 as the sample. The method of analysis used to test the hypothesis of Moderated Regression Analysis (MRA). The results of this study indicate that the effect of regional real revenue and general allocation fund has effect on capital expenditures, whereas revenue sharing fund have not an on capital expenditures. Moderating variables (economic growth) capable of moderating variable revenue sharing fund, but not able to moderate variable regional real revenue and general allocation fund on capital expenditure.